Implementasi Pola Pemuridan Yesus Menurut Injil Matius - Johannes Sembiring (Sekolah Tinggi Alkitab Jember, 2020)
Matthew does not emphasize the apostle's understanding of Jesus' disciples in his writings, but instead uses the term